Effect of pH on the Protective Action of Interferon in L Cells - Hallum, Jules V. (1968)
The pH of the solution in which interferon was applied to L cells determined the level of resistance developed against challenge with vesicular stomatitis virus (VSV). No inhibition of challenge virus was observed when interferon was applied to cells at pH 6.0. At pH 6.5, partial inhibition of VSV replication was observed and inhibition was maximum at pH 7.0. Evidence was obtained that interferon interacted with L cells at pH 6.0, but that resistance did not develop until the cells were placed in a medium at pH 7.0. These effects were explained by data showing that exposure of cells to a medium at pH 6.0 reversibly inhibited both ribonucleic acid and protein synthesis.